UJI ORGANOLEPTIK DAN HEDONIK MADU HERBAL YANG TERBUAT DARI MADU KELULUT (Heterotrigona itama) DAN MINYAK ATSIRI KULIT KAYU MANIS (Cinnamomum burmannii Blume) - Muhammad Mirza; Siti Hamidah; Trisnu Satriadi (Jurnal Sylva Scienteae, 2026)
This study aims to analyze the effect of adding cinnamon bark essential oil (Cinnamomum burmannii) on the organoleptic characteristics and preference level (hedonic) of herbal honey based on kelulut honey (Heterotrigona itama). Five herbal honey formulations were tested with variations in essential oil levels, starting from without the addition of essential oil (F1) to the highest level (F5) of 0.300 ml of essential oil. Organoleptic tests of the aroma and taste of herbal honey used trained and semi-trained panelists, while the hedonic test used trained and semi-trained panelists with a scale of 0-5. Data analysis used one-way ANOVA and continued with the appropriate difference test to see the significance between treatments. The results showed that formulation F2 (15 ml honey + 0.075 ml essential oil) or the addition of 0.075 ml cinnamon bark essential oil to 15 ml of honey had the most preferred aroma and taste characteristics, and met the quality criteria based on SNI 8664:2018. On the other hand, increasing the concentration of essential oils above the optimal limit causes a significant decrease in sensory acceptance. It can be concluded that the formulation of herbal honey greatly determines the success of the product, both in terms of sensory characteristics and potential market acceptance.